ANALYSIS OF THE CURRENT SITUATION OF HISTORICAL CULTURAL RELICS PROTECTION IN UZBEKISTAN - Fan Yu Jian (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Uzbekistan is located at the heart of the ancient Silk Road and possesses abundant historical and cultural heritage resources. Historic cities such as Samarkand, Bukhara, and Khiva are not only symbols of Central Asian civilization but also important parts of the world cultural heritage. In recent years, with the development of tourism and the strengthening of international cultural cooperation, the government of Uzbekistan has gradually increased its efforts in the protection of historical relics and ancient architecture. However, influenced by factors such as economic development, urbanization, environmental changes, and the shortage of professional specialists, the protection of historical relics in Uzbekistan still faces many challenges. This paper analyzes the current situation of historical relic protection in Uzbekistan, discusses the major protection models, existing problems, and future development directions, and proposes relevant suggestions based on international experience. The study aims to provide references for cultural heritage protection research in Central Asia.